Real-world treatment of metastatic hormone-sensitive prostate cancer in the USA, Europe and Asia - Goebell, Peter; Raina, Rutika; Chen, Stephanie; Rege, Sanika; Shah, Ruchit; Grossman, Jamie Partridge; Waldeck, A. Reginald (Future Oncology, 2024)
Aim: To characterize real-world patients with metastatic hormone-sensitive prostate cancer (mHSPC) and treating physicians and evaluate treatment trends and baseline concordance versus guidelines internationally. Materials & methods: Retrospective, cross-sectional data from the Ipsos Global Oncology Monitor database 2018-2020 were used for descriptive analysis of mHSPC patients, treating physicians and treatment utilization. Results: Among the 6198 mHSPC patients from five countries, the most common treatment was either androgen deprivation therapy (ADT) monotherapy or first-generation androgen receptor inhibitor + ADT. Second-generation androgen receptor inhibitor use was only initiating but increasing over the study period. Conclusion: Despite contemporaneous guidelines recommending treatment intensification of ADT in combination with novel antihormonals or docetaxel, 76.1% of reported mHSPC patients received non-guideline-concordant care.
CRIS-Team Scopus Importer:2024-04-12
Keywords: androgen antagonists; therapeutic use; antineoplastic agents; hormonal; therapeutic use; antineoplastic combined chemotherapy protocols; therapeutic use; guideline adherence; health care surveys; trends; neoplasm metastasis; practice guidelines as topic; practice patterns; physicians' trends; prostatic neoplasms; drug therapy; prostatic neoplasms; pathology